Computing economic loss in cases of wrongful death - King, Elizabeth M.; Smith, James P., 1943-; Rand eBooks (Santa Monica, CA : RAND, 1988)
This report outlines a new method for computing economic loss in cases of wrongful death. The authors use the human capital (or lost economic output) approach because it dominates actual litigation. In this conceptual model, economic loss is the value of the decedent's lost future productivity, market and nonmarket. The methodology includes seven elements: (1) base-year incomes, (2) salary growth, (3) worklife discounts, (4) nonmarket loss, (5) personal consumption offset, (6) taxes, and (7) discount rates. The methodology can be applied in a wide range of tort cases besides wrongful death.
"The Institute for Civil Justice."
Includes bibliographical references (p. 119-124)
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Arbitration and award; Insurance, Aviation; Wrongful death -- Economic aspects -- United States; Electronic books